(untitled) (Journal of Economic Research & Business Administration, 2015)
The paper provides a SWOT-analysis of Oil and Gas Sector of Kazakhstan and main problems of its development. The dynamic development of the oil and gas industry is very important for the economy of Kazakhstan. Nowadays, the oil and gas industry plays a crucial role in the economy of the Republic of Kazakhstan. According to the results of the analysis, it is pointed the opportunities of the industry, perspective objects for investment, as well as the risks for the industry, that should be considered and evaluated for the development of the sector. Given the fact that most of the developed oil fields are in the final stage, the most urgent task at present facing the country is finding new ways for the efficient production of oil and, especially, petroleum products to support the sustainability and competitiveness of the economy of the Republic of Kazakhstan.